Exploratory Study of Intracutaneous Histamine Stimulation in Patient Populations with Chronic Pruritus - Athanasios Tsianakas; Nadine Nippe; Christina Maria Hamper; Anna Friederike Cordes; Claudia Zeidler; Martin Schmelz; Sonja Ständer (Medical Journals Sweden, 2018)
Chronic pruritus can be a diagnostic sign of an underlying disease. In the intracutaneous histamine test, histamine (one of the best-known inducers of pruritus) may cause different reaction patterns depending on the underlying disease. The aim of this study was to determine if an intracutaneous injection of histamine can differentiate between the causes of chronic pruritus and thus be used as a diagnostic test in chronic pruritus of unknown aetiology. A total of 140 subjects with chronic pruritus with various dermatological, systemic or neurological diseases were included. The intracutaneous histamine test was performed once on each subject. Erythema, wheal and pruritus intensity were measured and analysed. Significantly greater wheal size was observed in patients with systemic or multifactorial causes. In general, there was a significant correlation between age and wheal size. Also, noticeable differences were found between males and females regarding pruritus and wheal size. In summary, the exact type of chronic pruritus could not be clearly determined based on the results of the intracutaneous histamine test. However, the results provide valuable insights into specific reaction patterns to experimental histamine-induced itch, e.g. sex-specific differences in the neurophysiology of pruritus, which should be considered in future studies.